Strategy for Integrating RTRW-Based Disaster Education to Control Land Use in Protected Natural Areas - Elsa Nur Aida; Hariyanto Hariyanto; Eva Banowati; Rahma Hayati; Erni Suharini (Universitas Lambung Mangkurat, 2026)
This study analyzes the implementation of the Regional Spatial Plan (RTRW) in controlling land use within natural protection areas of Salatiga City. It focuses on land use conformity, influencing factors, and environmental implications. A mixed-method approach was employed, with data collected through field observations, in-depth interviews, and document analysis. Data were analyzed using data reduction, data display, and conclusion-drawing techniques. The results show that RTRW implementation is not yet optimal, as some land uses remain inconsistent with the spatial plan, particularly in areas under development pressure. Supporting factors include regulatory availability and local government commitment, while inhibiting factors involve weak supervision, limited inter-agency coordination, and low public awareness. These conditions may reduce the ecological functions of protected areas. SWOT and QSPM analyses indicate that strengthening spatial planning education, improving supervision, and enforcing regulations are key priorities to support sustainable land use control in natural protection areas.